Sweet taste signaling and the formation of memories of energy sources - De Araujo, Ivan E. (Frontiers in Systems Neuroscience, 2011)
The last decade witnessed remarkable advances in our knowledge of the gustatory system. Application of molecular biology techniques not only determined the identity of the membrane receptors and downstream effectors that mediate sweetness, but also uncovered the overall logic of gustatory coding in the periphery. However, while the ability to taste sweet may offer the obvious advantage of eliciting rapid and robust intake of sugars, a number of recent studies demonstrate that sweetness is neither necessary nor sufficient for the formation of long-lasting preferences for stimuli associated with sugar intake. Furthermore, uncoupling sweet taste from ensuing energy utilization may disrupt body weight control. This minireview examines recent experiments performed in both rodents and Drosophila revealing the taste-independent rewarding properties of metabolizable sugars. Taken together, these experiments demonstrate the reinforcing actions of sugars in the absence of sweet taste signaling and point to a critical role played by dopamine systems in translating metabolic sensing into behavioral action. From a mechanistic viewpoint, current evidence favors the concept that gastrointestinal and post-absorptive signals contribute in parallel to sweet-independent sugar acceptance and dopamine release.